PERANANAN KEPEMIMPINAN KEPALA DESA TERHADAP PENINGKATAN PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DI DESA LERPAK - Zainal Abidin Zain; Cucu Hayati; Hanifah (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2023)
This research project is designed to assess the level of involvement of village heads in participatory decision-making processes within Lerpak Village. The findings obtained from this study reveal that the participation of village heads remains rather limited, leaving a substantial portion of the village population feeling excluded from decisions that directly impact their lives. Village heads tend to make decisions unilaterally, often neglecting meaningful dialogue or adequate consultation with the villagers. Several factors contribute to this limited engagement of village heads, including the need for improved communication skills, a lack of understanding regarding the significance of community involvement, limited institutional support, and a desire to maintain a firm grip on power. This article delves into the broader implications of these research findings, particularly concerning the enhancement of community participation in decision-making processes not only in Lerpak Village but also in similar rural communities. The recommendations put forth in response to these findings include the provision of communication skills training for village heads, with the hope that this will stimulate positive transformations in the practice of participatory decision-making, ultimately promoting inclusivity and effective governance in such communities.